Слабый принцип инвариантности для решений стохастического реккурентного уравнения в банаховом пространстве - Коваль, В.А. (Український математичний журнал, 1995)
We show that, in a Banach space, continuous random processes constructed by using solutions of the difference equationX n =A n X n+1+V n , n=1, 2,..., converge in distribution to a solution of the corresponding operator equation.